2020
DOI: 10.1140/epjst/e2020-000119-3
|View full text |Cite
|
Sign up to set email alerts
|

To the theory of ferrohydrodynamic circulating flow induced by running magnetic field

Abstract: We present results of theoretical modelling of macroscopic circulating flow induced in a drop of ferrofluid by oscillating running magnetic field. The drop is placed in a narrow flat channel filled by a non-magnetic liquid. The aim of this work is development of a scientific basis for a progressive method of address drug delivery to thrombus clots in blood vessels with the help of the magnetically induced circulation flow. Our results show that the oscillating running field allows inducing the carrier fluid fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the beginning, a drop of the nanoparticle suspension is injected in the centre of the channel and a Gaussian concentration profile is assumed at zero time. This study is the continuation of our two previous works [6,7] dealing with a flat channel and covering only short time scales (after setting on the field) when the nanoparticle concentration profile remains unchanged. These first studies demonstrated that efficient recirculatory flows can only be generated in heterogeneous alternating magnetic fields which in their turn induce heterogeneous nanoparticle concentration profiles.…”
Section: Introductionmentioning
confidence: 71%
“…In the beginning, a drop of the nanoparticle suspension is injected in the centre of the channel and a Gaussian concentration profile is assumed at zero time. This study is the continuation of our two previous works [6,7] dealing with a flat channel and covering only short time scales (after setting on the field) when the nanoparticle concentration profile remains unchanged. These first studies demonstrated that efficient recirculatory flows can only be generated in heterogeneous alternating magnetic fields which in their turn induce heterogeneous nanoparticle concentration profiles.…”
Section: Introductionmentioning
confidence: 71%